Revealing the dominant metacognitive activities of high school students in solving central tendency and dispersion problems based on gender - Henra, Kiki; Budayasa, I Ketut; Ismail (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Research on the relationship between gender and metacognition in mathematical problem-solving has yielded inconsistent findings. Some studies suggest that gender influences metacognitive activities, while others report no significant differences. This study seeks to explore metacognitive activities during each stage of statistical problem-solving among two 12th-grade students with contrasting gender expressions: a feminine-expressing female and a masculine-expressing male. The instruments utilized in this research include the Bem Sex Role Inventory (BSRI) gender questionnaire, a mathematical ability test, a statistical problem-solving task, and an interview guide. Data collection was conducted in two phases: the BSRI questionnaire and mathematical ability test were used to classify participants, followed by problem-solving tasks and semi-structured interviews to capture their metacognitive processes. Employing a descriptive exploratory design with a qualitative approach, the study applied thematic analysis to organize and interpret data from task performance and interview transcripts. These findings were further synthesized into hierarchical diagrams to illustrate the dominance of metacognitive components at different problem-solving stages. Results indicate that the feminine-expressing female predominantly utilized metacognitive knowledge, specifically declarative knowledge, during the problem-understanding phase. In contrast, the masculine-expressing male demonstrated more reliance on metacognitive regulation, particularly in planning and monitoring, during the problem-implementation stage. These findings underscore the importance of developing inclusive curricula and differentiated teaching strategies to enhance metacognitive skills across diverse student populations.